Strictly teacher-researchers? The influence of a professional RE conference on primary RE teachers' agency and self-identities as teacher-researchers. Issue 3 (3rd July 2021) - Salter, Emma; Tett, Prof Lyn
ABSTRACT: This paper investigates the influence of a professional Religious Education (RE) conference on a small group of English Primary teachers' emerging identities as teacher-researchers. It is framed by analysis of agency as a means of examining how teachers can become capable producers of knowledge as active partners in dialogue with critical others. The paper argues that attending the conference played a role in increasing teachers' professional identify and agency because it provided a novel context of action in teachers' professional lives. Teachers were made aware of a much broader professional community to which they had legitimate membership where knowledge exchange and professional validation was intensified. The conference enabled reflexive thinking that disrupted teachers' 'taken for granted' habits and beliefs by offering new ways of seeing, being and acting, and in which they could forecast teacher-research as a feasible, relevant and purposeful aspect of their professional lives.